Melia Kaplan-Hartnett: capstone - Kaplan-Hartnett, Melia, artist (Colorado State University. Libraries, 2026)
The artist's statement: My artwork is full of abstract repetition within lines and shapes. I am drawn to the action of layering with oils, and am fascinated by how, in depicting ambiguous realms, my paintings end up looking playful. My inspiration is rooted in nature and experiences of living with diabetes. I am fashioned by the internal human body and combine natural elements to form my paintings. I have always found peace from existing in places outside our chaotic world. Seeing vivid color that is alive in vines and blossoms, and not unloved structures that all mesh together. This abstract process begins with messy sketches drawn with watercolor pencils. Then I map out a rough idea of shapes and forms, drawing loose interpretations from my memory and the natural world. I add water to the marks, creating more fluidity, while leaving some marks alone. Once I start painting, I explore an intuitive process, repeating lines all over the canvas, covering up moments, and re-thinking the forms before adding more layers to the surface. I love how each brush stroke brings physical movement to the fibers, almost hinting that the canvas is alive. My paintings bring out playful qualities and vivid colors that spark conversation. For example, "Can you come get me?" is a painting from 2025 where I re-created a memory while incorporating natural elements in the space. It is full of soft greens and yellows in the background with purple bubbles in the foreground. There are pockets of raw canvas peeking through, with clear gesso and glazed areas to add depth. These ambiguous shapes offer the viewers a movement to think about what they see or who this reminds them of. They might see faces, an unfamiliar place, or feel a certain energy from the painting. An artist whom I have drawn inspiration from is Clayton V Colvin, an American painter. His work explores an experimental process of creating spaces through geometry by combining painting and drawing. Colvin's work deals with concepts around memory and sometimes depicts people. A series entitled "pre space mountain" is one I have been particularly drawn to. "in nashville" is a painting within the series from 2010. The background represents a sketch of an unknown interior space, with blocky lines and cylinders. While the foreground holds transparent pastel bubbles. As my painting process is developing, I am working with the flux and flows of coming up with ways to meld nature, memory, and the body. By studying artists such as Colvin and like-minded painters, I continue to grow and change with this medium. I hope that viewers can find their own stories within the layers and find meaning in the marks.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting